Assessment of Patient Satisfaction Attaining Primary Health Care Services at Health Centers in Mogadishu, Somalia - Abdi HA; Warsame MO; Adan MA; Hassan MA (Patient Preference and Adherence)
Hassan Ali Abdi,1 Mohamed Omar Warsame,2 Mohamud Abdinor Adan,3 Mohamed Ahmed Hassan4 1Quality Assurance and Patient Safety, Federal Ministry of Health and Human Services, Mogadishu, Somalia; 2Department of Public Health, Federal Ministry of Health and Human Services, Mogadishu, Somalia; 3Contract Management, Federal Ministry of Health and Human Services, Mogadishu, Somalia; 4MEAL, IRC, Mogadishu, SomaliaCorrespondence: Mohamed Omar Warsame, Email diirshe143@gmail.comBackground: Patient satisfaction in healthcare a crucial aspect of quality assessment, especially in resource-limited settings like Mogadishu, Somalia, where challenges in service quality persist due to socioeconomic and infrastructural constraints. It plays a significant role in evaluating the overall healthcare experience and provides valuable insights into healthcare system strengths and weaknesses.Objective: This study aimed to assess patient satisfaction in primary health care facilities in Mogadishu to identify areas for improvement.Methodology: A facility-based cross-sectional survey of 358 patients was conducted from August 2023 to November 2023; Data was collected through questionnaires and analyzed using SPSS software. Quantitative data was analyzed using appropriate statistical methods, such as descriptive statistics and chi-square tests, to examine the relationships between patient satisfaction and various factors the statistical significance was declared at p-value < 0.05. Ethical approval was obtained from the Ministry of health Somalia before data collection permission was also obtained from the health facility in charges.Results: While a majority of respondents, 71.5% express overall satisfaction with the healthcare services provided, there were significant concerns regarding empathy, privacy, facility cleanliness, and waiting times. There is a statistically significant association between patients’ visit frequency and their perceptions of various healthcare aspects. Patients who visited the healthcare facility 2– 4 times expressed significantly more positive perceptions of healthcare providers’ competence (p < 0.020), empathy (p < 0.009), time spent (p < 0.001), pharmacy services (p < 0.001), and facility cleanliness (p < 0.001) when compared to those with first-time visits or more frequent visits.Conclusion: The study highlights the importance of addressing communication gaps, enhancing facility hygiene, and reducing waiting times to improve patient satisfaction. To enhance patient satisfaction and overall healthcare quality, recommendations include healthcare provider training, facility hygiene upgrades, and the implementation of strengthened privacy protocols in Mogadishu’s primary healthcare facilities.Keywords: patient satisfaction, primary, healthcare, services and health centers